In silico analysis reveals the co-existence of CRISPR-Cas type I-F1 and type I-F2 systems and its association with restricted phage invasion in Acinetobacter baumannii - Yadav, Gulshan; Singh, Ruchi (Frontiers in Microbiology, 2022)
Introduction: Acinetobacter baumannii, an opportunistic pathogen, rapidly acquires antibiotic resistance, thus compelling researchers to develop alternative treatments at utmost priority. Phage-based therapies are of appreciable benefit; however, CRISPR-Cas systems are a major constraint in this approach. Hence for effective implementation and a promising future of phage-based therapies, a multifaceted understanding of the CRISPR-Cas systems is necessary. Methods: This study investigated 4,977 RefSeq genomes of A. baumannii from the NCBI database to comprehend the distribution and association of CRISPR-Cas systems with genomic determinants. Results: About 13.84% (n=689/4977) isolates were found to carry the CRSIPR-Cas system, and a small fraction of isolates, 1.49% (n= 74/4977), exhibited degenerated CRISPR-Cas systems. Of these CRISPR-Cas positive (+) isolates, 67.48% (465/689) isolates harboured type I-F1, 28.59% (197/689) had type I-F2, and 3.7% (26/689) had co-existence of both type I-F1 and type I-F2. Co-existing type I-F1 and I-F2 systems are located distantly (~1.733 Mb). We found a strong association of CRISPR-Cas systems within STs for type I-F1 and I-F2, whereas the type I-F1+F2 was not confined to any particular ST. Isolates with type I-F1+F2 exhibited a significantly high number of mean spacers (n= 164.58 ±46.41) per isolate as compared to isolates with type I-F2 (n=82.87 ±36.14) and type I-F1 (n=54.51 ±26.27) with majority targeting the phages. Isolates with type I-F1 (p-value <0.0001) and type I-F2 (p-value < 0.0115) displayed significantly larger genome sizes than type I-F1+F2. A significantly reduced number of integrated phages in isolates with co-existence of type I-F1+F2 compared with other counterparts was observed (p-value =0.0041). In addition, the isolates carrying type I-F1+F2, did not exhibit reduced resistance and virulence genes compared to CRISPR Cas(-) and CRISPR Cas (+) types I-F1 and type I-F2, except for bap, abaI, and abaR. Conclusion: Our observation suggests that the co-existence of type I-F1 and F2 is more effective in constraining the horizontal gene transfer and phage invasion in A. baumannii than the isolates exhibiting only type I-F1 and only type I-F2 systems.